PENYELESAIAN HUKUM TERHADAP PELAKU KECELAKAAN LALU LINTAS - Kadri; Fahmi; Harahap, Irawan (Collegium Studiosum Journal, 2024)
Law Number 22 of 2009 concerning Road Traffic and Transportation, specifically Article 310 paragraph (4), states that accidents causing the death of a person due to the negligence of the perpetrator can result in criminal sanctions. This article specifies that anyone who, due to their negligence, causes a traffic accident that results in the death of another person can be sentenced to a maximum of 6 (six) years in prison and/or a fine of up to IDR 12,000,000.00 (twelve million rupiah). The method used is sociological legal research. Based on the research findings, it is known that the rights of the perpetrator and the victim in a traffic accident include that the perpetrator has the right to be treated in accordance with applicable legal principles, including the right to legal defense, the right to fair treatment in legal proceedings, and the right to amend their wrongdoing through rehabilitation or mediation if necessary. On the other hand, the victim of a traffic accident also has the right to compensation for the losses they have suffered, including medical expenses, property damage, and other losses. These rights must be guaranteed and fulfilled with full responsibility by the parties involved, whether the perpetrator, law enforcement officials, or other relevant parties. Legal resolution of traffic accident perpetrators based on Law Number 22 of 2009 concerning Road Traffic and Transportation in the jurisdiction of Polresta Pekanbaru indicates that this law provides a clear framework regarding the procedures for law enforcement against traffic accident perpetrators. The law emphasizes that perpetrators who violate traffic regulations and cause accidents must be held accountable for their actions. The legal process is expected not only to focus on imposing sanctions but also to provide space for the perpetrators to correct their mistakes through appropriate mechanisms, such as fines, imprisonment, or administrative sanctions.